The Future of Liver Elastography in the Field of Hepatology - Sporea, Ioan (Ultrasound International Open, 2017)
Ultrasound-based liver elastography is being increasingly used in clinical practice to help clinicians assess prognosis and recommend the most appropriate treatment in hepatology patients. In coming years liver elastography will probably be increasingly used as part of "point of care" ultrasonography.